From Digital Divide to Digital Opportunity: the Adoption of e-Tutoring in a Rural School District - Corrigan, Julie A. (Université d'Ottawa / University of Ottawa, 2011)
The ubiquity of Web 2.0 technologies has led to a seismic shift in the way educational services are delivered. It comes as no surprise then that e-tutoring—otherwise known as electronic or online tutoring—is quickly supplanting face-to-face tuition for reasons of both cost and convenience. While e-tutoring is an effective form of academic support for many students, its efficacy remains tenuous for those confronted with a digital divide that figures predominantly around geographic barriers, socio-economic status, and educational levels. Premised on diffusion research, this master's dissertation explores the implementation of an e-tutoring service known as Homework Help that has effected relatively low adoption rates. It uses a concurrent mixed-methods approach—including surveys, interviews, and focus groups—to examine the factors that have led to this low adoption rate. The results are presented via two journal articles situated within a larger meta-talk: The first article contrasts the adoption patterns apparent between rural and urban students, while the second article looks at the utility of diffusion research in examining educational technologies, as it explores the use of e-tutoring for applied stream students. The findings of this study suggest that rural and urban, as well as applied and academic student subgroups, differ in terms of their perception and adoption of e-tutoring. Implications for educational policy, especially in regards to rural education, are discussed.
Keywords: e-tutoring; e-learning; rural education; mixed methods; diffusion; distance education; adoption